2022
DOI: 10.1177/01945998221102810
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Presentation and Surgical Outcomes From a Prospective Multicenter Chronic Rhinosinusitis Study

Abstract: Objective Despite extensive research into chronic rhinosinusitis (CRS) epidemiology, presentation, and outcomes, there is scant knowledge on sex-specific differences. The objective of this study was to identify differences between male and female patients with CRS in baseline disease severity at presentation, choice for surgery vs continued medical treatment, and postoperative response. Study Design We evaluated data on demographic and health characteristics, clinical objective disease measures, and sinus-spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(37 citation statements)
references
References 62 publications
(113 reference statements)
5
23
0
Order By: Relevance
“…Prior data has consistently shown that adult female patients with CRS have worse QoL as evidenced by higher overall SNOT-22 scores, with the difference being mainly accounted for by the non-rhinologic domains. 1,2,6 One large, multicenter study has found that females reported significantly higher health related QoL outcomes compared to the male cohort despite similar objective measures of disease severity. 1 Mendolia-Loffredo et al described worse scores on patients' QoL measures (Rhinosinusitis Disability Index and the Chronic Sinusitis Survey) in female patients with CRS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior data has consistently shown that adult female patients with CRS have worse QoL as evidenced by higher overall SNOT-22 scores, with the difference being mainly accounted for by the non-rhinologic domains. 1,2,6 One large, multicenter study has found that females reported significantly higher health related QoL outcomes compared to the male cohort despite similar objective measures of disease severity. 1 Mendolia-Loffredo et al described worse scores on patients' QoL measures (Rhinosinusitis Disability Index and the Chronic Sinusitis Survey) in female patients with CRS.…”
Section: Discussionmentioning
confidence: 99%
“…1,2,6 One large, multicenter study has found that females reported significantly higher health related QoL outcomes compared to the male cohort despite similar objective measures of disease severity. 1 Mendolia-Loffredo et al described worse scores on patients' QoL measures (Rhinosinusitis Disability Index and the Chronic Sinusitis Survey) in female patients with CRS. 3 In this study, authors attributed the difference to higher incidence of This article is protected by copyright.…”
Section: Discussionmentioning
confidence: 99%
“…Females who underwent ESS had worse QoL scores preoperatively and postoperatively than males despite lower clinical measurement of disease severity. 39,46,47 Although females reported worse QoL scores preoperatively and postoperatively, one study found no significant difference in postoperative improvement based on sex. Differences noted were accounted for by comorbid conditions of depression and aspirin intolerance.…”
Section: Qolmentioning
confidence: 99%
“…Compared with their male counterparts, female patients with CRS have consistently been found to report greater symptom burden using the 22-item Sino-Nasal Outcome Test (SNOT-22), a CRS-specific survey, despite comparable or less severe findings on imaging or endoscopy. [7][8][9][10][11][12][13] By contrast, the results have been mixed when utilizing the EuroQol 5-Dimension (EQ-5D), a general health survey, with some studies demonstrating worse baseline scores for women with CRS 14 and others not identifying any gender differences. 15 Endoscopic sinus surgery (ESS) is a well-established treatment option for CRS that has broadly been shown to produce durable, long-term improvements in quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24][25] Given this association, there is reason to suspect that notable shifts in quality of life occur in the years following ESS that differentially affect female and male patients. Indeed, in studies that have examined the clinical outcomes of sinus surgery at sequential time points, the symptom burden has been found to be higher among female patients than male patients within the first 6 months post-ESS 11,12 before becoming comparable to that of male patients by 1 year after surgery. 6,26,27 Unfortunately, the follow-up time period in these reports has been short, generally 2 years or less, and long-term gender differences in postoperative outcomes have not been studied.…”
Section: Introductionmentioning
confidence: 99%